(3GdQhV GdLdi aj fSH Hfi Ydhis - (3CHh GdajV eMeO Hf eMeO Hf eMeO GHf YHO GdQGRb, GdSjO eQJVj GdMSjfj GdRHjOj,J (B1205 (3g` s ((3WGgQ Hf Ydhi Hf WGgQ Hf YHO Gddg GdgOGQ GdMOGO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa bQGHI fHjg haVdge Ydi SGFQ GdCee hHYO abO Medfi Ydi JCdja gPg GdQSGdI GdCN GdaGVd GdYdGeI Gdabjg GdSjO eUWai Hf GdEeGe Gdabjg GdeMOK GdSjO YHO GdQMef GdYjOQhS GdJQjei GdMSjfi s
(3BNQgG (B:s
(3hdge Pjhd eHGQcI ai cd GdCeUGQ HGQc Gddg ai YOOge , hdjcf gPG BNQ eGbUOfG , hGdMeO ddg ChdkG hBNQkG s
(3fSNI cJHJ Yf fSNI SfI (B1350 (3Yf fSNI cJHJ SfI (B1196(3g` YdjgG NW GdeDda GdeMahXI YfO GdSGOI GdhaGFjI HGdbGgQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B70s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs